Renewable Energy, Green Economic Growth and Food Security in Central Asian Countries: An Empirical Analysis - Kurmanov, Nurlan; Kabdullina, Gulmira; Baidakov, Assilbek; Kabdolla, Asylkhan (International Journal of Energy Economics and Policy, 2025)
The following paper explores an impact green economic growth, renewable energy consumption, and industrialization have on food security in Central Asian countries, namely Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. We used a POLS model to analyze relationships between selected factors and food security based on panel data for the period between 2001 and 2020, including variables such as the share of renewable electricity, green economic growth, level of industrialization, and arable land area. The results showed a positive impact green economic growth and industrialization have on food security in Central Asia, while renewable energy also contributes to its strengthening, although requires balanced resource management to prevent competition with agriculture. Country-by-country analysis has revealed some differences: Kazakhstan is facing the challenges of transitioning from fossil fuels, Kyrgyzstan and Tajikistan depend on international cooperation to implement renewable energy projects, Turkmenistan, despite having large natural gas reserves, needs to diversify energy resources, and Uzbekistan must find a balance between water resource management and energy needs in the face of a growing population. Results highlight the need for a tailored approach with policy recommendations including increased investment in green technologies, agricultural modernization support, energy industry’s balanced development, and international cooperation for sustainable development and food security promotion in Central Asia.